Receptivity of Boundary Layer over a Blunt Wedge due to Freestream Pulse Disturbances at Mach 6 - Jianqiang Shi; Xiaojun Tang; Zhenqing Wang; Mingfang Shi; Wei Zhao (International Journal of Aerospace Engineering)
Direct numerical simulation (DNS) of a hypersonic compressible flow over a blunt wedge with fast acoustic disturbances in freestream is performed. The receptivity characteristics of boundary layer to freestream pulse acoustic disturbances are numerically investigated at Mach 6, and the frequency effects of freestream pulse wave on boundary layer receptivity are discussed. Results show that there are several main disturbance mode clusters in boundary layer under acoustic pulse wave, and the number of main disturbance clusters decreases along the streamwise. As disturbance wave propagates from upstream to downstream direction, the component of the modes below fundamental frequency decreases, and the component of the modes above second harmonic components increases quickly in general. There are competition and disturbance energy transfer between different boundary layer modes. The nose boundary layer is dominated by the nearby mode of fundamental frequency. The number of the main disturbance mode clusters decreases as the freestream disturbance frequency increases. The frequency range with larger growth narrows along the streamwise. In general, the amplitudes of both fundamental mode and harmonics become larger with the decreasing of freestream disturbance frequency. High frequency freestream disturbance accelerates the decay of disturbance wave in downstream boundary layer.